Investigación del Impacto que ha generado la contratación de personas con discapacidad en el clima laboral de las 100 empresas privadas con mayores ingresos del Distrito Metropolitano de Quito. - Herrera Herrera, Rosa Gabriela (2014)
Pursuant to the requirements of current legislation established in Ecuador, about the establishment of the percentage for the inclusion of people with disabilities into the workplace, it was considered necessary to determine the impact that has existed in the various variables of the work environment of the 100 private companies with incomes of Metropolitan District of Quito. The research has deepened the reality of companies to hire staff with disabilities, make the changes around processes, infrastructure, innovation, interpersonal relationships need for supervision, among others. According to the study has shown that private companies with incomes of Quito, aim to ensure the welfare of its employees, without distinction, so that the working environment is not affected negatively, currently , organizations seek to eliminate paradigms about the inclusion of staff with disabilities through programs, training, guidelines in order to enhance working relationships with an optimal working environment.